The Role of the Rationality in Social Innovation - Bagong Suyanto, Nugroho Widyo Bharoto, (Opción, 2019)
This study was conducted to see what happens when there are conditions of the institutional void in a section on government agencies. This research was conducted by a qualitative approach through in depth interviews to research subjects and notes obtained during interview and field observation. As a result, the interest of the government agencies for the implementation of the work in the unit to run properly covered in the interests of employees to obtain a good career and comfort work. In conclusion, government employees are vulnerable to the influence of rules, abstinence and selective indiscretion.